2012
DOI: 10.1121/1.4730329
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of elastic properties in a trabecula using micro-Brillouin scattering and scanning acoustic microscopy

Abstract: Micro-Brillouin scattering (μ-BR) and a 200 MHz scanning acoustic microscope (SAM) with similar spatial resolutions were applied to evaluate tissue elastic properties in two directions in a trabecula. Acoustic impedance measured by SAM was in the range of 5–9 Mrayl. Wave velocities determined by μ-BR were in the range of (4.75–5.11) × 103 m/s. Both exhibited a similar trend of variation across the trabecula and were significantly correlated (R2 = 0.63–0.67, p < 0.01). μ-BR is useful for the evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…These values are consistent with literature data collected on rabbit femurs, where Young's moduli ranged from 6 -12 GPa for newly formed bone tissue and of 9 -17 GPa for mature bone tissue [23,57]. The values of wave velocity v are comprised between 4.77x10 3 and 5.41x10 3 m/s and are in agreement with the previous study on the same in vivo model [16] and in the same range as the results obtained in other studies characterizing wave velocities within bone trabeculae [41,42].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These values are consistent with literature data collected on rabbit femurs, where Young's moduli ranged from 6 -12 GPa for newly formed bone tissue and of 9 -17 GPa for mature bone tissue [23,57]. The values of wave velocity v are comprised between 4.77x10 3 and 5.41x10 3 m/s and are in agreement with the previous study on the same in vivo model [16] and in the same range as the results obtained in other studies characterizing wave velocities within bone trabeculae [41,42].…”
Section: Discussionsupporting
confidence: 89%
“…Micro-Brillouin scattering allows the assessment of the ultrasonic wave velocity of the tested material in the GHz range, without contact and nondestructively [38]. Micro-Brillouin scattering has been used to investigate bone wave velocity, in particular within the femoral head [39] or in a bone defect [40], as well as to assess bone anisotropic properties [41], bone structure and alignment [42], the effect of decalcification [43] and the effects of glycation [44].…”
Section: Introductionmentioning
confidence: 99%
“…These values are in good agreement with our previous studies in which we reported velocities in the range of 4.75-5.10 Â 10 3 m/s in bovine trabeculae. 15 Velocity values are in the range of 4.81-5.22 Â 10 3 and 4.83-5.00 Â 10 3 m/s in mature and new cortical bones of rabbit tibiae, respectively. ANOVA (p < 0.01, F ¼ 36.14) reveals significant differences between the average velocity in the M-L direction and those in the A-P and axis directions.…”
Section: Compressional Wave Velocities and Trabecular Shapementioning
confidence: 91%
“…SAM and l-BR have displayed similar trends in variation across the trabecula and were significantly correlated (R 2 ¼ 0.63, p < 0.01). 15 This result means that l-BR should be useful for the evaluation of tissue stiffness within a single trabecula. A recent bone l-BR study by our group showed a significant difference in the compressional wave velocity between mature and newly formed tissues.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, the anisotropy of the materials can be measured by in-plane rotation of the sample. We have previously applied [9]. However, the measurements of weak thermal phonons resulted in the lower measurement accuracy and longer measurement time than those of other ultrasonic methods, such as pulse techniques in the MHz range.…”
Section: Introductionmentioning
confidence: 99%